2009
DOI: 10.4049/jimmunol.0901032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lipoteichoic Acid as a Ligand for Draper in the Phagocytosis of Staphylococcus aureus by Drosophila Hemocytes

Abstract: Phagocytosis is central to cellular immunity against bacterial infections. As in mammals, both opsonin-dependent and -independent mechanisms of phagocytosis seemingly exist in Drosophila. Although candidate Drosophila receptors for phagocytosis have been reported, how they recognize bacteria, either directly or indirectly, remains to be elucidated. We searched for the Staphylococcus aureus genes required for phagocytosis by Drosophila hemocytes in a screening of mutant strains with defects in the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 60 publications
1
78
0
Order By: Relevance
“…CED-1 (40,41) and Draper (42,43), a Drosophila counterpart of CED-1, appear to bind proteins in the recognition of apoptotic cells by phagocytes. Draper also recognizes lipoteichoic acid, a cell wall component, as a ligand in the phagocytosis of S. aureus by hemocytes (34), suggesting a multiplicity of ligands for this receptor. In contrast, ligands for integrins in the recognition of apoptotic cells by phagocytes of C. elegans and Drosophila are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…CED-1 (40,41) and Draper (42,43), a Drosophila counterpart of CED-1, appear to bind proteins in the recognition of apoptotic cells by phagocytes. Draper also recognizes lipoteichoic acid, a cell wall component, as a ligand in the phagocytosis of S. aureus by hemocytes (34), suggesting a multiplicity of ligands for this receptor. In contrast, ligands for integrins in the recognition of apoptotic cells by phagocytes of C. elegans and Drosophila are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although the eater and draper genes are not located in the Nimrod gene cluster, the encoded proteins exhibit the characteristic NIM domain structure. Eater and Draper receptors have been demonstrated to bind bacteria [7][8][9]. NimC1 has been reported to be involved in the phagocytosis of bacteria [2], however no biochemical assays were performed to prove the interaction of NimC1 or other Nimrod proteins with bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis is a major cellular response among the self-defense strategies of Drosophila, which are employed to fight against infection with pathogenic bacteria, and its mechanism has been investigated in adult flies abdominally injected with bacteria, a surrogate procedure for septic infection (38,(41)(42)(43)(44)(45)(46). We previously reported that s 38 , a stress-responsive s factor of E. coli (47)(48)(49)(50)(51), is involved in the bacterial evasion of phagocytic killing in Drosophila (41).…”
mentioning
confidence: 99%
“…Bacteria were cultured with Luria-Bertani medium, supplemented with antibiotics when necessary, at 37˚C until the cultures reached the stationary phase of cell growth, after which they were harvested by centrifugation, washed with PBS, and used in the experiments. Hemocytes were isolated from third-instar larvae according to a standard procedure (62) with slight modifications (44). l(2)mbn, a larval hemocytederived cell line, was maintained with Schneider's Drosophila medium (Life Technologies Japan, Tokyo, Japan) containing 10% (v/v) heatinactivated FBS at 25˚C, as described previously (44).…”
mentioning
confidence: 99%
See 1 more Smart Citation